Is Psychology Headed in the Right Direction?. (July 2017) - Kross, Ethan
Is psychology headed in the right direction? In this essay, I share my views on the answer to this question. I begin by describing how recent advances in technology, heightened levels of interdisciplinary collaboration, a renewed emphasis on considering the broader implications of basic psychological research, and field-wide efforts to encourage optimal research practices have combined to tilt psychology's trajectory upward. I then offer three suggestions for how to maintain the field's upward slanting course: (a) collaborate more to build cumulative knowledge, (b) improve the way we communicate contextual factors in psychological research, and (c) examine the psychological effects of technology. I conclude by offering a single piece of advice for new researchers and a few closing comments.